The slow component of oxygen uptake of insulated muscular groups measured with NIRS during intermittent isometric contractions in humans - E. Tam; M. Bertucco; C. Capelli (Physiological Reports)
Abstract When exercising in the severe‐intensity domain, oxygen uptake (V̇O2) does not reach a steady state since it slowly and continuously drifts due to the appearance of the slow component of V̇O2 (V̇O2sc). V̇O2sc has been customarily evaluated by measuring V̇O2 using pulmonary gas exchanges, including the contribution of the metabolic expenditure of the respiratory muscles, heart, and muscles recruited for stabilizing the posture, etc. We assessed the muscular oxygen uptake (mV̇O2, in μM·s−1) of flexor digitorum superficialis by using near‐infrared spectroscopy (NIRS) during brief arterial occlusions imposed over repeated, cyclic isometric hand grips performed at two different percentages (25%; 50%) of maximal voluntary contraction (MVC). mV̇O2 was significantly larger at 50% MVC than at 25% MVC at all the time points (p < 0.05) as expected, apart from the values at the 3rd minute. Secondly, mV̇O2 increased linearly at 25% of MVC (mV̇O2 = 1.73 + 0.108 × min; r2 = 0.993; p < 0.0033) and at 50% of MVC (mV̇O2 = 2.41 + 0.240 × min; r2 = 0.956; p < 0.0223) from the 3rd minute of exercise onwards; the slopes of the two linear regressions were significantly different (p < 0.0232). We suggest that the V̇O2sc of mV̇O2 occurring during intermittent isometric contractions can be assessed with NIRS during brief complete arterial occlusions regularly interspersed in the series of contractions. In addition, the technique can discriminate the rates of increase of mV̇O2 corresponding to different percentages of MVC.